The existence of Entarnoeba Gingivalis in the oral cavity with mild oral hygiene - Rachmawati, Emma (Universitas Padjadjaran, 2007)
Entamoeba gingivalis is protozoa (non-pathogen amoeba) that lives in the oral cavity and act as opportunistic parasite. The parasite is most common found within oral cavity with advance periodontal disease. This study aimed to find the existence Entamoeba gingivalis within oral cavity with mild oral hygiene. The study was conducted by making preparation of plaque taken from patient's oral cavity with mild oral hygiene. The degree of oral hygiene was determined by using Silness and Loe Index and Ramfjord Periodontal Index. The number of Entamoeba gingivalis was gained by counting them from the preparation examined under microscope. The result demonstrates that mild oral hygiene has a high percentage of Entamoeba gingivalis is that 80 % either for various plaque index or ages.